Attitudes toward Psychological Help and Coping Behavior of Senior High School Students - Musni, Ralph Vendel Emborgo (Technium Social Sciences Journal, 2021)
Senior High School students are further uncovered to numerous shapes of psychological trouble (i.e. enthusiastic, social and scholastic issues) that can lead to passionate precariousness and sadness (Peterson, 2002). With this situation, guidance services are regarded vital. This study seeks to investigate among senior high school students on their attitude towards psychological help and their coping behavior. The study used the descriptive survey method among the Grade-11 and 12 students in one of the Universities in Cagayan de Oro City. Finding of the study revealed that Grade 11 and Grade 12 respondents were mostly 18 years of age and dominated by males. STEM strand was the biggest in group and most respondents came from the Public schools. Of the ATSPPHS four factor measurements, Factor-3 Interpersonal Openness got the highest mean value. Factor-4 Confidence in Mental Health Professional got the lowest mean value. Thus, the Grade -11 and 12 respondents have slight tendency and somehow positive attitude to seek professional and psychological help when they are confronted with problems and issues in life. Grade-11 coping response was through listening to music while the Grade-12 students’ coping response would to apologize to people whom they have in conflict with. Moreover, the result showed no significant difference on the respondents’ attitudes toward psychological help based on the four factors of ATSPPHC. However, there was a significant difference on students’ attitude sunder HUMMS and GAS strands toward psychological help particularly on factors two and three namely: Tolerance of Stigma Associated with Psychological Help and Interpersonal Openness respectively. The study revealed that there was no significant difference on the respondents’ coping behavior and attitude towards psychological help. It is imperative to conclude that there is a strong need to promote more awareness on the guidance related programs to encourage more Grade 11 and 12 students to trust and submit themselves for counseling whenever they face personal problems and issues in life. It therefore recommended the following: Develop a program that will address the student’s attitude and coping behavior toward seeking psychological help; Enrich the general guidance services program of the school; School personnel, teachers and counselors must undergo enrichment trainings, seminars to better understand why some students display high anxiety, fear, and depression in the campus.